The relationship between attachment style and creativity: The mediating roles of LMX and TMX. Issue 6 (2nd November 2019) - Kirrane, Melrona; Kilroy, Steven; Kidney, Rachel; Flood, Patrick C.; Bauwens, Robin
ABSTRACT: The capacity and willingness of employees to deploy their creativity in the pursuit of organisational goals is a cornerstone of many organisations' competitive advantage. Drawing on the actor-context interactionist perspective on creativity, we propose that insecure attachment styles act as distal antecedents that reduce employee creativity through the mediating role of social exchange relationships (i.e., leader-member exchange [LMX] and team-member exchange [TMX]). To test the proposed model, data were gathered from 192 employees and their respective supervisors in 12 engineering organisations. Hierarchical multiple regression and Monte Carlo mediation using the lme4 and mediation packages in R was performed to test the proposed hypotheses. Results revealed that while high quality LMX and TMX relationships are positively associated with creativity, insecure attachment styles have significant negative effects on employees' perception of the quality of their LMX and TMX relationships, which, in turn, lead to lower creative output. Taken together, our results reveal the important influence of insecure attachment styles on creativity and in particular highlight the central role of leader-follower and team member relations as underlying mechanisms in this regard. We discuss the implications of our findings for research and practice.